An analysis of directive illocutionary acts in the complex: lockdown 2020 movie - Sugiantini, Ni Made Putri; Maharani, Putu Devi; Winartha , IB Gde Nova (Journal of Language and Applied Linguistics, 2021)
This goal of this study is to describe the types of directive illocutionary act and to find out the most dominant directives speech act performed by the characters in The Complex: Lockdown movie through the theory of Speech Act by Kreidler (1998) and supported by the theory from Searle (1979). In analyzing the data, descriptive qualitative method is used. This study found 73 data of directive illocutionary act performed by the characters in the movie. In addition, it was found the most dominant directives used is command with 27 (37%) occurences followed by question with 23 (32%) occurences. Both types of directive is the most commonly used because the characters are forced to do a certain task quickly with a limited time to think. That causes they gave command to other and asked question frequently during the emergency situation after several bio-weapon attacks. The least dominant types of directive speech act are found namely; request with 16 (22%) occurences and followed by suggestion with 7 (9%) occurences.